2018
DOI: 10.1123/ijsnem.2017-0199
|View full text |Cite
|
Sign up to set email alerts
|

Sweat Sodium, Potassium, and Chloride Concentrations Analyzed Same Day as Collection Versus After 7 Days Storage in a Range of Temperatures

Abstract: The purpose of this study was to determine the effect of storage temperature on sodium ([Na]), potassium ([K]), and chloride ([Cl]) concentrations of sweat samples analyzed 7 days after collection. Using the absorbent patch technique, 845 sweat samples were collected from 39 subjects (32 ± 7 years, 72.9 ± 10.5 kg) during exercise. On the same day as collection (PRESTORAGE), 609 samples were analyzed for [Na], [Cl], and [K] by ion chromatography (IC) and 236 samples were analyzed for [Na] using a compact ion-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Differences in sample storage temperature seem to have minimal impact on sweat electrolyte concentrations, as (Baker et al 2018a) found negligible changes in sweat [Na + ], [Cl − ], and [K + ] between same-day analysis and post-7-day storage (in Parafilm-M ® -sealed vials) at − 20 °C, 8 °C, and 23 °C. There is a paucity of research measuring the effect of storage conditions on other sweat constituents.…”
Section: Sample Storage and Analytical Techniquesmentioning
confidence: 90%
See 1 more Smart Citation
“…Differences in sample storage temperature seem to have minimal impact on sweat electrolyte concentrations, as (Baker et al 2018a) found negligible changes in sweat [Na + ], [Cl − ], and [K + ] between same-day analysis and post-7-day storage (in Parafilm-M ® -sealed vials) at − 20 °C, 8 °C, and 23 °C. There is a paucity of research measuring the effect of storage conditions on other sweat constituents.…”
Section: Sample Storage and Analytical Techniquesmentioning
confidence: 90%
“…Sample storage methodology is another potential source of variability in sweat constituent concentrations and, not surprisingly, one of the most important factors is proper sealing of the sample vials. When well-sealed and stored at room temperature (23-25 °C), refrigeration (4-8 °C), or frozen (− 20 °C) for up to 7 days, minimal sweat evaporation and minimal change in sweat [Na 2+ ], [Cl − ], and [K + ] has been reported (Baker et al 2018a;Bergeron et al 2011;Jones et al 2008). However, when vials were capped but not sealed with Parafilm-M ® for 3 or 5 days, 19% and 32% sample evaporation has occurred; storing the vials in a plastic bag was associated with 16 and 27% sample evaporation, respectively.…”
Section: Sample Storage and Analytical Techniquesmentioning
confidence: 99%
“…Therefore, samples are sometimes stored at room temperature until chemical analysis. The selected storage durations (0, 7, 28 days) were chosen to allow for comparison with previous research [ 11 ]. In addition, storage for 7 days is a realistic time span for field work and 28 days was selected to determine the impact of a significantly longer storage duration.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst several studies have described the best techniques for sweat collection and subsequent chemical analysis [ 8–10 ], the best practices for sweat sample storage are yet to be quantified. It has been suggested that the use of inconsistent storage conditions (i.e., temperature and duration) can lead to substantial errors [ 11–14 ]. Dziedzic et al [ 12 ] reported a ≤ 14% increase in sweat sodium concentration when analyzed immediately after sampling compared to after refrigeration at 7°C for 7 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation